Counter-terrorism strategies in a fragmented international legal order meeting the challenges - Herik, L. J. van den (Larissa J.); Schrijver, Nico, 1954- (Cambridge University Press, 2013)
In this important contribution to international discourse, the authors examine the relationship between different branches of international law and their applicability to the problem of terrorism and counter-terrorism.